Julius seizure, a Drosophila Mutant, Defines a Neuronal Population Underlying Epileptogenesis. Issue 3 (1st March 2017) - Horne, Meghan; Krebushevski, Kaitlyn; Wells, Amelia; Tunio, Nahel; Jarvis, Casey; Francisco, Glen; Geiss, Jane; Recknagel, Andrew; Deitcher, David L
Abstract: Epilepsy is a neural disorder characterized by recurrent seizures. Bang-sensitive Drosophila represent an important model for studying epilepsy and neuronal excitability. Previous work identified the bang-sensitive gene slamdance ( sda ) as an allele of the aminopeptidase N gene. Here we show through extensive genetic analysis, including recombination frequency, deficiency mapping, transposon insertion complementation testing, RNA interference (RNAi), and genetic rescue that the gene responsible for the seizure sensitivity is julius seizure ( jus ), formerly CG14509, which encodes a novel transmembrane domain protein. We also describe more severe genetic alleles of jus . RNAi-mediated knockdown of jus revealed that it is required only in neurons and not glia, and that partial bang-sensitivity is caused by knockdown in GABAergic or cholinergic but not glutamatergic neurons. RNAi knockdown of jus at the early pupal stages leads to strong seizures in adult animals, implicating that stage as critical for epileptogenesis. A C-terminal-tagged version of Jus was generated from a fosmid genomic clone. This fosmid fusion rescued the bang-sensitive phenotype and was expressed in the optic lobes and the subesophageal and thoracic abdominal ganglia. The protein was primarily localized in axons, especially in the neck connectives, extending into the thoracic abdominal ganglion.